Analisis Pengaruh Pengetahuan Perpajakan, Motivasi, Nilai Sosial, Dan Self Efficacy, Terhadap Minat Berkarir Menjadi Konsultan Pajak - Yolis Silvester; Febriati Febriati; Ali Afif; Aris Setiawan (Program Studi Akuntansi Universitas Panca Bhakti, 2026)
This study aims to analyze and determine the influence of tax knowledge, motivation, social values, and self-efficacy on students' interest in becoming tax consultants. This study used a quantitative descriptive method and primary data collection using a questionnaire. The sampling method used was purposive sampling. The population in this study were active students of the Accounting Department of the Faculty of Economics and Business, Panca Bhakti University, Widya Dharma University, and Tanjung Pura University, graduating in the classes of 2023, 2022, and 2021, who had taken taxation courses. The sample size was 104 respondents. This study used primary data obtained through the distribution of a Google Form link containing a questionnaire, distributed online. Data analysis used multiple regression analysis. The results of this study indicate that motivation, social values, and self-efficacy positively influence accounting students' interest in becoming tax consultants, while tax knowledge has no effect on accounting students' interest in becoming tax consultants.